TEACHING ENGLISH IDIOMS TO UNIVERSITY STUDENTS: CHALLENGES AND EFFECTIVE PEDAGOGICAL STRATEGIES - Azizakhon Zulfikorova (Modern American Journals, 2025)
Idiomatic phrases are integral to the mastery of English language fluency. They enrich communication, express cultural values, and enhance learners’ pragmatic skills. However, idioms can be challenging for non-native speakers because their meanings cannot be interpreted literally. University students, even with their advanced proficiency, still encounter obstacles in understanding and utilizing idioms in appropriate contexts. This article explores the significance of idioms in English language learning, outlines challenges faced by students, and evaluates pedagogical approaches for teaching idioms effectively at the tertiary level. Through classroom observations and survey responses from undergraduate English majors, the study finds that contextualized teaching methods, integration of multimedia, and task-based learning activities enhance higher levels of idiomatic competence. The article concludes by recommending a systematic incorporation of idioms into the university curriculum to improve both linguistic and cultural skills.
Keywords: idioms, figurative language, English teaching, university students, pedagogy